2022
DOI: 10.1038/s41586-022-04833-8
|View full text |Cite|
|
Sign up to set email alerts
|

Androgen receptor blockade promotes response to BRAF/MEK-targeted therapy

Abstract: Treatment with molecularly-targeted therapy has revolutionized cancer care, including BRAF/MEKtargeted melanoma therapy. However responses are heterogenous and frequently not long-lasting. Novel strategies to target resistance are needed. We studied a cohort of patients with resectable metastatic melanoma treated with neoadjuvant BRAF/MEK-targeted therapy (n=52) and noted a strong sexual dimorphism in response to treatment, with female patients demonstrating signi cantly higher rates of a major pathologic resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 58 publications
2
51
0
2
Order By: Relevance
“…In our analysis, the gender group showed a bias phenomenon regarding CD8 + Runx3 + , CD8 + CTSW + cytotoxic, and CD8 + exhaustion. Recently, a series of clinical and experimental studies reported that gender has a significant impact on the effectiveness of antitumor immunotherapy ( 65 67 ). In patients with colorectal cancer or melanoma, the androgen receptor (AR) mediated signaling pathways impaired the stem-cell like feature of CD8 + T cells, resulting in CD8 + T cell exhaustion in male tumor patients, whereas female patients with lower AR expression and androgen levels gained better antitumor immunity ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, the gender group showed a bias phenomenon regarding CD8 + Runx3 + , CD8 + CTSW + cytotoxic, and CD8 + exhaustion. Recently, a series of clinical and experimental studies reported that gender has a significant impact on the effectiveness of antitumor immunotherapy ( 65 67 ). In patients with colorectal cancer or melanoma, the androgen receptor (AR) mediated signaling pathways impaired the stem-cell like feature of CD8 + T cells, resulting in CD8 + T cell exhaustion in male tumor patients, whereas female patients with lower AR expression and androgen levels gained better antitumor immunity ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic or pharmacological suppression of AR activity in melanoma cells hinders their proliferation [ 10 ]. Very recently, Vellano et al demonstrated that AR blockage promoted a better response to BRAF/MEK-targeted therapy in melanoma patients, thus improving recurrence-free survival [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sex hormone signaling pathways are likely to affect cancer susceptibility and prognosis through multiple intrinsic and extrinsic mechanisms. The latest study by Vellano et al revealed that the expression of androgen receptors was significantly increased in male patients during BRAF/MEK targeted therapy and was associated with therapeutic resistance [ 81 ]. Yang et al identify that AR signaling accelerates the transition from stem cell-like CD8 + T cells to terminally exhausted CD8 + T cells in males, leading to sex-biased anti-tumor immunity.…”
Section: Sex Disparities In Sex Hormone and Hormone Receptor-mediated...mentioning
confidence: 99%